Some Existence Results for Impulsive Nonlinear Fractional Differential Equations with Closed Boundary Conditions - Hilmi Ergören; Adem Kiliçman (Abstract and Applied Analysis)
We investigate some existence results for the solutions to impulsive fractional differential equations having closed boundary conditions. Our results are based on contracting mapping principle and Burton-Kirk fixed point theorem.